Newborn Care Practices at Home: Effect of a Hospital-based Intervention in Sri Lanka - Senarath, Upul; Fernando, D.N.; Rodrigo, Ishani (My University, 2007)
The aim of the present study was to evaluate the effect of an essential newborn care (ENC) training programme for maternity ward staff in improving newborn care practices after hospital discharge. A before-and-after study was conducted in the community involving mothers who had given birth in two hospitals in the Puttalam district in Sri Lanka. The intervention was a 4-day training programme and primarily aimed at increasing knowledge and skills of ENC among health care providers in the maternity units of these hospitals. Before the intervention, 144 mother–newborn pairs were followed-up and interviewed at their households within 28–35 days of delivery. Three months after the intervention, 150 mother–newborn pairs were interviewed at home. Results revealed that there was a significant improvement in umbilical cord care practices at home following the intervention. Application of ‘surgical spirit’ on umbilical cord has declined from 71.5% in the pre-intervention to 45.3% in the post-intervention samples (p < 0.001). Pre-intervention breastfeeding rates were high, and there wasn't any further improvement in the post-intervention. There was a 35% reduction in the proportion of newborns who developed any undesirable health events at home (p < 0.05). Findings suggest that the implementation of a comprehensive 4-day training programme of ENC for maternity ward health professionals can be followed by a significant improvement in mothers' practices on care of umbilical cord and clinical outcomes of newborns.